The enigmatic invasive Spartina densiflora : A history of hybridizations in a polyploidy context - Fortune, P.M. (2008)
The aim of this study was to explore the origin of the invasive Spartina densiflora by analysing samples from the native region (South America) and from a recently colonized area (California). A combination of various molecular data (chloroplast and nuclear sequences, molecular fingerprint) and ploidy level estimations was used to answer the question whether the reticulate phylogenetic pattern previously detected in S. densiflora was restricted to California, or alternatively, whether a more ancient hybrid origin preceded formation of this species in its native area. We found that this species is heptaploid in both its native and introduced range. Identification of nuclear homeologous sequences indicate that this species has a reticulate origin in its native range, involving a lineage related to the hexaploid clade formed by S. alterniflora, S. foliosa, and S. maritima, and another lineage related to the sub‐Antarctic endemic S. arundinacea that provided the chloroplast genome. The samples from California displayed similar multilocus patterns to the samples from Chile, supporting the hypothesis that this species originated on the southeast American coast (Argentina), from where it eventually spread to the west coast of South America (Chile) first and to the Northern Hemisphere (California) later.